Therapeutic Strategies in Pulmonary Hypertension of the Newborn: Where Are We Now? - Sanchez Luna, Manuel; Luisa Franco, M; Bernardo, Belen (Current Medicinal Chemistry, 2012)
Despite recent advances, Persistent Pulmonary Hypertension of the Newborn (PPHN) still represents an important challenge for neonatologists. The care of newborns with PPHN requires meticulous therapeutic and ventilation strategies including, besides the stabilization of the newborn, the use of selective pulmonary vasodilators as inhaled Nitric Oxide (iNO). However, not all the neonates with PPHN are responsive to this clinical approach. Recent studies have proposed the use of alternative therapies to iNO, when it is not available, or there is no or only a transitory response. Sildenafil, a phosphodiesterase 5 inhibitor, appears as a frequent used therapy in refractory forms of PPHN. The aim of this review is to analyze the current therapeutic strategies in PPHN with special emphasis on iNO.
Keywords: PPHN